أعمال أحكام قواعد مناهج التنازع - شويع، محمد حسناوى (جامعة الكوفة - كلية القانون, 2021)
تركز هذه الورقة البحثية على عرض أهم أحكام طرق حل النزاع بين القوانين. إذا كانت قواعد الإسناد التقليدية لا تزال سائدة في حل النزاعات بين القوانين المتنافسة والوصول إلى القانون المعني بالنزاع من خلال طريقة محايدة وغير مباشرة، مما يعني أن الأطراف المتنازعة لا تعرف حتى أيا من القوانين المتنافسة هو المتخصص في حل التزاحم بين القوانين إلا بعد استشارة قاعدة الإسناد التي تعمل على هذا التحديد على أساس وجود وسائل مساعدة مثل الجنسية أو محل الإقامة. ثم تحديد قانون الجنسية أو البلد الأصلي وبالإشارة إلى هذا القانون المعني يبدأ مرحلة جديدة في التركيز العلاقة مع الفرع القانوني الدقيق من داخل القانون المختص بحيث يتم حل نزاع الأطراف وفق هذه الطريقة غير المباشرة في تحديد القانون ذي الصلة ولم تمنع أسلوب قاعدة الإسناد غير المباشرة من ظهور طريقة لمنهج مباشر تتبعه قواعد إسناد مباشرة وقريبا من هذا المنهج قواعد البوليس المدنية إذ تعمل القواعد الأخيرة وفقا لأسلوب مباشر في تحديد القانون الذي يجب تطبيقه بشكل مباشر، وهى طريقة تمنع إلى حد ما مرحلة النزاع لأن الطرفين يعرفان ومن لحظة عرض الخلاف أو النزاع على القضاء كون القانون العراقي هو المختص أو غيره. مثال ذلك تكييف العلاقات القانونية فالقانون العراقي هو المختص ومباشرة لتكييف العلاقات القانونية أو تحديد طبيعتها إذا طلب منه القيام بذلك بشكل مباشر وغير تنازعي. وعلى مقربة من الطريقة المباشرة لقواعد الإسناد مع التطبيق المباشر، هناك قواعد موضوعية تم إنتاجها من خلال المعاملات التجارية الدولية الخاصة التي تعمل وفقا لطريقة الصيغة المباشرة في تحديد القانون المعمول به، لكنها قفزت أكثر من ذلك لأنها تعمل مباشرة لحل نزاع الطرفين بشكل مباشر وليس فقط حل النزاع بين القوانين. This research paper focuses on presenting the most important provisions of the methods of resolving conflict between laws. If the traditional rules of support are still prevalent in resolving conflicts between competing laws and access to the law concerned with conflict through an indirect, neutral method, meaning that the conflicting parties do not yet know which of the competing laws is The specialist in resolving the conflict only after consulting the base of support that works on that identification based on the presence of auxiliary means such as nationality or domicile, then the determination of the nationality law or the home country and with reference to that law concerned begins a new phase in focusing the relationship with the precise legal branch from within the relevant law so that the dispute of the parties is resolved according to And this indirect method in determining the relevant law did not prevent the emergence of a method for a direct approach taken by the rules of direct attribution and approaching the rules of civil police. The latter rules work according to a direct method in determining the law that should be applied directly, it is a method that to some extent prevents the stage of conflict because the parties know and once The dispute between them and presenting it to the judiciary is that the Iraqi law is the one concerned or any other, such as adapting legal relations, so the Iraqi law is a matter H directly in his competence to adapt legal relationships or determine their nature if requested to do so directly and non-competently. And close to the direct method of attribution rules with direct application, there are objective rules that were produced by private international commercial transactions that operate according to the direct formula method in determining the applicable law, but it jumped further than that, as it works directly to resolve the parties ’dispute directly and not only does it resolve conflict between laws.
Keywords: الأحكام القضائية -- النزاعات المسلحة -- التشريعات العراقية -- التنظيمات القانونية